2013
DOI: 10.1068/a45732
|View full text |Cite
|
Sign up to set email alerts
|

Import Flows: Extraregional Linkages Stimulating Renewal of Regional Sectors?

Abstract: We examine the role of regional import flows for renewal of regional industries. The hypothesis is that imports stimulate renewal of local industries by being vehicles for technology diffusion and means by which local firms can exploit advantages of global specialisation. We find robust and positive relationships between high-quality imports and renewal of regional exports, where the latter are measured by the introduction of novel export products of local firms. Connectedness to international markets via impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(46 reference statements)
0
11
0
1
Order By: Relevance
“…A promising research avenue is to assess the role of extra-regional linkages more systematically, as new combinations are likely to depend on both local and non-local inputs. Andersson, Bjerke, and Karlsson (2013) found a positive effect of high-quality imports on the introduction of new high-quality export products in regions, suggesting import spillover effects at the regional scale. The same study found that openness of a regional economy had a positive influence on such economic renewal in regions.…”
Section: The Need For More Geographical Wisdommentioning
confidence: 93%
“…A promising research avenue is to assess the role of extra-regional linkages more systematically, as new combinations are likely to depend on both local and non-local inputs. Andersson, Bjerke, and Karlsson (2013) found a positive effect of high-quality imports on the introduction of new high-quality export products in regions, suggesting import spillover effects at the regional scale. The same study found that openness of a regional economy had a positive influence on such economic renewal in regions.…”
Section: The Need For More Geographical Wisdommentioning
confidence: 93%
“…However, research has also shown that international import networks can be a vehicle for the inflow of knowledge and technology from abroad, and a stimulus for new ideas conducive to the renewal and upgrading of a region's export sector (Malecki ; Andersson et al . ). Connected and porous communities can also benefit from human capital inflows, including entrepreneurial in‐migration (Stockdale ; Atterton ; Bosworth ), social capital accrual (Putnam ), and access to opportunity‐rich business networks, which are increasingly supported by digital networks (Lin ).…”
Section: A Cohesive and Connected Countryside?mentioning
confidence: 97%
“…Strong ties in terms of IO relationships between sectors in the same area mean extensive propagation channels that can transmit crises across sectors and space (Acemoglu, Ozdaglar, andTahbaz-Salehi 2013, Jovanovic 1987). Additionally, having a closely knit local industrial structure with limited interaction to outside competition and/or cooperation may lead to lock-in effects, reduce knowledge flows and the adaptive capacity of regions in the face of adversity (Grabher 1993, Boschma and Iammarino 2009, Shutters, Muneepeerakul, and Lobo 2015, Andersson, Bjerke, and Karlsson 2013. Uzzi (1997) discusses these issues as the 'paradox of embeddedness' whilst studies such as Becattini and Rullani (1996), Maskell and Malmberg (2007) and Bathelt and Cohendet (2014) all highlight the need for combinations of local and global knowledge networks to avoid the 'cognitive myopia' (Buciuni and Pisano 2018) identified by Grabher (1993) in Germany's Ruhr Valley.…”
Section: Regional Embeddedness Resilience and Resistancementioning
confidence: 99%